KANDUNGAN KADAR PROTEIN PADA ASI BAYI 0-6 BULAN - Fitrotin Azizah; Fulatul Anifah (Universitas Muhammadiyah Surabaya, 2020)
Breast milk has advantages compared to other milk, including the temperature of breast milk being the same as body temperature, cleanliness being guaranteed, and the content of breast milk plays an essential role in the growth of brain cells and the development of the nervous system. This study aims to describe the content of protein levels in breast milk. The samples used in this study were five samples of breast milk obtained from mothers who had children aged 0-6 months in the Surabaya area, using the Kjeldahl method. The average protein content of breast milk (is 12.764%). The protein content of breast milk has a higher protein content in laboratory tests because it adapts to the needs of the baby. Breast milk has a high protein content. The protein in breast milk is mostly whey protein rather than casein. The higher casein content will form relatively hard lumps in the baby's stomach, making it difficult to digest. The whey in formula milk contains lactoglobulin, which can cause allergies in babies. Mothers are expected to follow WHO recommendations to provide exclusive breastfeeding for 0-6 months and continue breastfeeding until the child is two years old.Keywords : Protein, content, breast milk, babies